Charcot neuroarthropathy of the hand in a diabetic patient after upper extremity trauma - Kulaklı, Fazıl; Çulha, Canan; Akdemir, Seval (The European Research Journal, 2018)
Charcot neuroarthropathy is a progressive degenerative arthritis which affects nearly every joint of the body associated with an underlying central or peripheral neurological disorder and can cause severe disability. The joints most frequently involved are lower limbs especially foot, shoulder and elbow. However, Charcot neuroarthropathy of the hand is quite rare. Herein, we present a 50-year-old diabetic female patient with Charcot neuroarthropathy of the right hand after upper extremity trauma. Major or minor traumas in diabetic patients can increase the risk of Charcot neuroarthropathy on upper extremity as a complication of diabetes mellitus.